Rim enhancement, drainage, and inflammatory response in patients with anterior versus posterior lingual abscesses (Annals of Medical Research, 2025)
Aim: Lingual abscesses are rare but potentially serious infections of the tongue, with limited data available in the literature. This study aimed to compare the clinical, radiological, and laboratory features of anterior and posterior lingual abscesses and evaluate the impact of drainage on patient outcomes.Materials and Methods: This retrospective case series included 17 patients diagnosed with lingual abscess between February 2019 and March 2025. Patients were categorized based on anatomical localization (anterior vs. posterior). Demographic data, symptoms, laboratory values (WBC, CRP, etc), computed tomography findings, treatment modalities, and outcomes were analyzed. Subgroup comparisons were performed based on abscess location, drainage status, and rim enhancement.Results: Of the 17 patients, 10 had anterior and 7 had posterior abscesses. Posterior abscesses were larger and associated with significantly longer hospital stays (p = 0.004). Drainage was associated with significantly shorter hospitalization (p = 0.005) and greater reduction in white blood cell counts by day 5 (p = 0.046). Rim enhancement on computed tomography was not significantly associated with clinical or laboratory outcomes. Streptococcus species were the most commonly isolated pathogens. No major complications or airway interventions were required.Conclusion: Posterior lingual abscesses demonstrate a more severe clinical course than anterior abscesses. Surgical drainage is associated with improved inflammatory markers and faster clinical recovery. Rim enhancement alone may not reliably reflect disease severity. These findings support the importance of early diagnosis and individualized management based on anatomical location and clinical progression.
Keywords: Tongue disease; Abscess; Drainage; Mediators of inflammation